GROWTH PERFORMANCE OF CALVES IN KHYBER PAKHTUNKHWA, PAKISTAN - Ahmad; S.; Z. U. Haq; G. Jabbar; Y. Muhammed; S. Sultan; Ihsanullah; D. Khan (Journal of Animal and Plant Sciences, 2013)
Data from Feed Lot Fattening farms: operating under Livestock and Dairy Development Board; having at least one buffalo calf were collected for analyzing comparative performance of buffalo-calves for beef production. A total of 1408 animals present in 56 farms scattered over eight districts of Khyber Pakhtunkhwa were studied. In order to control for the variables that could potentially affect the growth but the data for which is not available e.g. ambient temperature and humidity, nature of green fodder, ingredients of concentrates, the model is augmented with location, year and specie specific fixed effects. The model fitted the data and suggests 30 percent of the variation in the daily weight gain as explained by variation in the independent variables. Mean weight at purchase were 139.4 ±1.77 and 131.4±1.40 kg of buffalo and cattle calves which fattened over a mean period of 94 days at different seasons in two years. The species, over the fattening period, gained mean weight of 70 and 72 kg for which the farmers received extra Rs. 3211.8 and Rs. 3030.6 per buffalo and cattle calf, respectively. The study estimates the effect of specie (buffalo and cow), year (2007 and 2008), location of farm (the eight districts), initial calf weight and season on the growth performance measured as daily weight gain of cows and buffaloes. The growth model while controlling for other variables, suggests that daily weight gain during winter is higher as compared to other seasons. However, the effect of herd size and specie on daily weight gain is non-significant. On overall, the combined effects of location and year on daily weight gain are significant implying that overlooking these effects in the analysis may result biased estimates similar to omitted variable in regression analysis.
Keywords: Buffalo calves; feed-lot fattening; growth performance